Initial investment in diversity is the efficient thing to do for resilient forest landscape restoration - Nef, Danny P.; Gotor, Elisabetta; Wiederkehr Guerra, Gabriela Patricia; Zumwald, Marius; Kettle, Christopher J. (Frontiers Media, 2021)
This paper explores in detail the economic cost of improved integration of genetic diversity into restoration projects and tests the assumption that the beneﬁts accruing from better integration of diversity exceed the costs. Using a bottom-up cost model, we analyse different FLR cost drivers, integrating genetic quality, in relation to the total costs of a range of tree-based restoration interventions. The results indicate that the integration of genetic diversity into the management and planning of landscape restoration projects increased the costs incurred at the beginning of FLR interventions. However, despite this initial increase in costs the overall costs of restoration decreased substantially, due to cost savings relating to replacement costs of replanting.